2011
DOI: 10.1002/ps.2088
|View full text |Cite
|
Sign up to set email alerts
|

Display female‐specific doublesex RNA interference in early generations of transformed oriental fruit fly, Bactrocera dorsalis (Hendel)

Abstract: The results clearly indicate that RNAi is heritable through the expression of specific siRNA in early generations of transformed oriental fruit fly. These results can broaden the understanding of sex-related developmental mechanisms in the fly, and also offer a possible molecular approach for pest control in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The egging devices were set into each cage of treatments (above), and the number of eggs per device was either counted directly or estimated by filling the eggs into a 1 mL syringe when this was possible (1 mL of eggs was calibrated to contain about 1.8 × 10). Eggs collected from treated and control cages were gently flushed from the bottles onto a mesh strainer (100 mesh nylon gauze).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The egging devices were set into each cage of treatments (above), and the number of eggs per device was either counted directly or estimated by filling the eggs into a 1 mL syringe when this was possible (1 mL of eggs was calibrated to contain about 1.8 × 10). Eggs collected from treated and control cages were gently flushed from the bottles onto a mesh strainer (100 mesh nylon gauze).…”
Section: Methodsmentioning
confidence: 99%
“…The oriental fruit fly, Bactrocera dorsalis (Hendel), is one of the most damaging fruit pests in the world and a serious pest in southern China . It is a polyphagous pest that attacks more than 150 host plants, including numerous commercial fruit and vegetables . Damage caused by B. dorsalis consists of oviposition stings in fruits by adult females and subsequent larval feeding and decay on the fruit pulp.…”
Section: Introductionmentioning
confidence: 99%
“…B. dorsalis is listed in quarantine restrictions and is considered to be one of the most important pest species for its high invasive ability, wild distribution and economic significance (Clarke et al ., ). Because of its appropriate size, impressive reproductive capacity and short developmental duration, it has been used as a model for the Bactrocera complex in multiple projects, including genetic diversity (Wan et al ., ), development (Chen et al ., ), reproductive behaviour (Shelly et al ., ) and molecular control (Chen et al ., ; Li et al ., ), and ranging from basic biology studies to RNA interference (RNAi) applications. Although the availability of the whole genome sequence would facilitate research into this pest, work on this is still in progress (Bactrobase: http://www.bactrobase.org/).…”
Section: Introductionmentioning
confidence: 99%
“…The high breakage ratio of the Ac p‐ RTA‐Bddsx expression unit might result from mitotic recombination between homologous chromosomes. In our experience from previous Bddsx f RNAi studies, the exogenous transgene has been shown to be unstable in transgenic lines . The Bddsx f RNAi transgene became undetectable in the F8 generation following Ds‐Red screening (unpublished observation).…”
Section: Resultsmentioning
confidence: 89%
“…An RTA‐Bddsx gene driven by the actin 5C promoter of B. dorsalis in the piggyBac vector was constructed. The piggyBac transposon, which has a broad host range, including B. dorsalis, requires application through embryonic microinjection . The expression vector, pBac(PUb‐DsRed), contained the DsRed marker gene for transgene integration screening.…”
Section: Introductionmentioning
confidence: 99%